Imaging Artifacts on Synthesized Mammogram: What a Radiologist should Know! - Gulati, Shrea; Dhamija, Ekta; Anand, Roshni (Indian Journal of Radiology and Imaging, 2022)
Synthesized mammogram is a new technique that involves reconstruction of a two-dimensional (2D) image from the tomosynthesis images rather than separate acquisition of a standard 2D mammogram. The advent of a synthesized mammogram (s2D) has helped in reducing radiation exposure. The technique of back projection used in reconstruction makes the appearance of these images different from a standard 2D mammogram. Because this is a relatively new technique, it is associated with a learning curve. Hence, it is important for the new radiologists and technicians to be aware of certain common artifacts encountered while using s2D images, which may hinder interpretation. In this pictorial review, we would like to highlight the common artifacts encountered while reading synthesized mammographic images.
Keywords: artifacts; C-view; digital mammography; synthesized mammogram; tomosynthesis